2011
DOI: 10.1007/s12291-011-0120-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Correlates with HIVmRNA in Serodiscordant Heterosexual HIVpartners of Nigerian Origin

Abstract: We recruited 59 individuals of known HIV serostatus after informed consent however, 44 were serodiscordant heterosexual partners [serodiscordant seronegative (SSN group) and serodiscordant seropositive (SSP group)] while 15 were seronegative healthy individuals (SNH). In the case-control study we choose to determine Malondialdehyde (MDA) concentration as a marker of lipid peroxidation index (oxidative stress) spectrophotometrically and quantify HIV mRNA by Real Time-nucleic acid sequence based amplification as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Gaman and her colleagues [23] reported similar patterns of OS increase in stage B/C of chronic lymphocytic leukaemia (CLL) patients. Ibeh et al using serodiscordant HIV patients showed a high OS condition in serodiscordant-seropositive individuals against their seronegative partners [24]. In a further study, he observed an increased oxidative stress condition in different stages of HIV disease in patients undergoing antiretroviral therapy in Nigeria, where over 50% of the nontreatment group was in stage 2 of the infection [25].…”
Section: Ros In Hiv Infection: Do They Differ In the Different Stagesmentioning
confidence: 93%
See 1 more Smart Citation
“…Gaman and her colleagues [23] reported similar patterns of OS increase in stage B/C of chronic lymphocytic leukaemia (CLL) patients. Ibeh et al using serodiscordant HIV patients showed a high OS condition in serodiscordant-seropositive individuals against their seronegative partners [24]. In a further study, he observed an increased oxidative stress condition in different stages of HIV disease in patients undergoing antiretroviral therapy in Nigeria, where over 50% of the nontreatment group was in stage 2 of the infection [25].…”
Section: Ros In Hiv Infection: Do They Differ In the Different Stagesmentioning
confidence: 93%
“…Peroxidation of membrane lipids can have several outcomes, such as increased membrane rigidity, decreased activity of membrane-bound enzymes, altered activity of membrane receptors (e.g. sodium pumps), altered permeability (increased permissibility), formation of hydrophobic centres that approaches the external phase, alteration of protein structure, mutagenicity (resulting from DNA/RNA damage or binding) and inhibition of growth and protein synthesis [24]. This is caused by the high nucleophilic properties of decomposed aldehyde products formed during lipid peroxidation, which enables them to react with electrophilic sites such as amino and thiol groups [42].…”
Section: Lipid Peroxidation Products: a Possible Biomarker Of Hiv Dismentioning
confidence: 99%
“…Lipid peroxidation is still rampant despite effective viral control. While a couple of studies report decreased levels in markers of lipid peroxidation in ART-medicated patients, as compared with those not receiving ART, multiple studies have shown persistent statistically significant increases in hydroperoxides, isoprostanes, and malondialdehyde in ART-treated HIV-infected individuals, compared to seronegative controls [103,113,[133][134][135][136][137][138][139]. Interestingly, two independent groups have determined in patient blood samples that the levels of peroxide species and oxidative stress are higher in patients on protease inhibitor (PI) based regimens, as compared with those in individuals on non-nucleoside reverse transcriptase inhibitor (NNRTI) based regimens, implicating a role for the protease inhibitor class in induction or exacerbation of oxidative stress [138,140].…”
Section: Oxidative Stress In the Era Of Artmentioning
confidence: 99%